2023
DOI: 10.15619/nzjp/48.3.06
|View full text |Cite
|
Sign up to set email alerts
|

Intersection of the elements of evidence-based practice in interdisciplinary stroke rehabilitation: A qualitative study

Abstract: Evidence-based practice (EBP) is a foundational approach to clinical decision-making that integrates scientific research; clinical expertise; and patient preferences, values and circumstances. The purpose of this study was to explore the intersection of the three elements of EBP among an interdisciplinary stroke rehabilitation team. An exploratory qualitative descriptive design was used to examine the intersection of elements through a focus group with the allied health members of an interdisciplinary stroke r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The first aim of this study was to understand what factors influence how physiotherapy interventions for PLwSCI are selected and the role of evidence in decision making. The results show that although physiotherapists currently use evidence to make treatment decisions, it is only one part of a complex balance of many factors [ 16 ]. Physiotherapists in this study identified difficulties incorporating evidence in their practice.…”
Section: Discussionmentioning
confidence: 99%
“…The first aim of this study was to understand what factors influence how physiotherapy interventions for PLwSCI are selected and the role of evidence in decision making. The results show that although physiotherapists currently use evidence to make treatment decisions, it is only one part of a complex balance of many factors [ 16 ]. Physiotherapists in this study identified difficulties incorporating evidence in their practice.…”
Section: Discussionmentioning
confidence: 99%
“…Rehabilitation is an interactive process in which the relationships between professionals and SUs are crucial and collaborative. According to Vingerhoets, Hay-Smith, and Graham ( 7 ), it is crucial to look at the intersection of SUs' values, professionals' expertise, and evidence from research. People who take part in the collaboration enrich the work by bringing their own unique perspective and different experiences to it.…”
Section: Introductionmentioning
confidence: 99%